Comparing Acid and Enzymatic Hydrolysis Methods for Cellulose Nanocrystals (CNCs) Obtention from Agroindustrial Rice Husk Waste - Ricardo Hernández Pérez; René Salgado Delgado; Alfredo Olarte Paredes; Areli Salgado Delgado; Edgar García Hernández; Atenas Medrano Valis; Fryda Martínez Candia (Journal of Nanotechnology)
Agroindustrial residues represent a serious environmental problem in the world; in this case, the polluting rice husk, present in the rice fields of Morelos State, is one source of incalculable biomass. The aim of this study was to assess two viable and optimized procedures for obtaining nanocellulose from these wastes. The sieved samples included 4 treatments with different grain sizes (sieves # 10, 15, 30, and 50) and three replicates. They were then processed by an alkaline treatment (NaOH) 5%, bleaching with sodium hypochlorite, followed by pretreatment with 0.65% hydrochloric acid (HCl). After drying, the cellulose was subjected to acid hydrolysis with (H2SO4) at 64%, and was compared to an enzymatic hydrolysis complex. This complex was formed of D-(+) cellobiose and endo-1,4-β-D-glucanase from Acidothermus cellulolyticus. End products were sonicated and dialyzed until they reach a neutral pH. Finally, the nanocellulose was characterized by FTIR, DSC, XRD, SEM, and TEM. Evident results recognize the nanocellulose (NC) synthesis by both routes, with greater contaminants generated in the medium by the acid hydrolysis. It is much more feasible and faster to achieve with enzymatic hydrolysis, less aggressive for the environment, and higher performance. In future trials, the cost-benefit of using the enzyme complex should be assessed as an alternative to replace acid hydrolysis.Key words: acid hydrolysis, enzymatic hydrolysis, waste, rice husk, Oryzasativa L, cellulose nanocrystals (CNCs).